Deficit irrigation in peach orchards under water scarcity conditions - Duarte, A.C. (2020)
The irrigation patterns in two peach orchards, located in the central eastern region of Portugal, called “Beira Interior”, and the effect of different amounts of irrigation on the total production and fruit quality were evaluated. The experiment was conducted in 2016, in two different orchards, and included three treatments correspondent to three different flow rates per tree: 8, 12 and 16 l/hour. The water balance, which included the water supplied by rain and irrigation and the crop evapotranspiration, was developed. At harvest, crop production, pulp firmness and percentage of the total soluble solids were evaluated. There were no significant differences between treatments in the average production per tree. However, in one of the orchards production increased with the volume of irrigation. In the same orchard, fruit firmness decreased with the increasing water supply. Total soluble solids had decreased with the increasing water supply in both orchards, probably as a consequence of the dilution effect due, directly, to the water incorporated in the fruits, or, indirectly, to the larger fruits produced by the trees that were irrigated more. In general, the treatments used in this study as well as in the farmers’ practices, the supplied water was in deficit, but the farmers tend empirically to follow closely the evolution of evapotranspiration.